2021
DOI: 10.1155/2021/3098374
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Online and Offline Interactive Teaching Method in Clinical Anesthesiology Teaching

Abstract: Objective. To explore whether better teaching effect can be achieved by applying the online and offline interactive teaching method to clinical anesthesiology teaching. Methods. Sixty-three students in grade three majoring in anesthesiology of Wenzhou Medical University were selected as research objects and randomly divided into 2 groups. The experimental group (32 students) adopted the online and offline interactive teaching method. The control group (31 students) adopted the traditional teaching method. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Similar results were substantiated by the findings of Wang et al . [ 21 ] where 87.5% of the students think that the mixed teaching method is better than the traditional teaching method.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were substantiated by the findings of Wang et al . [ 21 ] where 87.5% of the students think that the mixed teaching method is better than the traditional teaching method.…”
Section: Discussionmentioning
confidence: 99%
“…Wang, Q. applied the online and offline interactive teaching methods to the teaching of clinical anesthesiology and achieved better teaching results. He found that in the process of online teaching of clinical anesthesiology, there is a significant positive correlation between learner interaction and learning achievement in online teaching, and this correlation coefficient is higher than that in traditional teaching [22].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary vocational education has clearly professional, and traditional teaching methods based on theoretical education reduce student learning efficiency [7]. To do this, educators change the way they think about education, live classroom education, integrate educational strategies, personalize educational objects, achieve student initiatives in learning, effective teacher-student interaction, and diverse educational assessment goals [10].…”
Section: Introductionmentioning
confidence: 99%